Identifying the critical success factors and their relevant aspects for renewable energy projects; an empirical perspective - Maqbool, Rashid; Rashid, Yahya; Sultana, Saira; Sudong, Ye (Journal of Civil Engineering and Management, 2018)
Owed to their enormous impact on the sustainable development of energy security, climate change, and the economy, multiple renewable-energy projects are carried out around the world, both in developed and in developing countries. Since the construction of renewable energy project is an entrepreneurial activity, there is a big concern about the success of such projects. Although pertinent literature suggests several methodologies to enhance the success of various projects, renewable-energy projects are still overlooked. This study identifies multiple critical success factors (CSFs), required for renewable-energy projects. Using a sample of 272 firms working on renewable energy projects in Pakistan, a quantitative and causal study was undertaken to identify the critical success factors (CSFs). Structural equation modeling (SEM) was applied to test and verify hypothesis. The results show that there is a strong direct dependency of project success over the proposed factors, however environmental factors are found to be the only predominant CSFs which show the significant indirect effect over project success. The study expected to contribute towards and widen up the existing knowledge base for the project performance of renewable energy projects by adding on the findings regarding critical success factors.